2011
DOI: 10.1007/s10522-011-9326-7
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces stress response and hormetically modulates wound healing ability of human skin fibroblasts undergoing ageing in vitro

Abstract: Wound healing becomes impaired in several diseases and during ageing. A commonly used model for the study of wound healing is a scratched monolayer of cells in vitro, which is convenient for the analysis of the cellular and molecular changes occurring during the two phases of wound healing, namely cell migration and cell proliferation. Cell migration, which is the primary event to occur during initial wound healing, is inversely dependent on the number of focal adhesions (FA) that attach cells to the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 16 publications
(23 reference statements)
1
58
0
Order By: Relevance
“…Such hormetins may be categorized as: (1) physical hormetins, such as exercise, hypergravity, heat and radiation; (2) biological and nutritional hormetins, such as infections, micronutrients, spices and other natural and synthetic compounds; and (3) psychological hormetins, such as mental challenge and focused attention or meditation. Several review and research articles have been published with respect to testing potential anti-aging hormetins, such as heat shock, irradiation, hypergravity, curcumin, kinetin, rosmarinic acid, ferulic acid and food restriction (Barone et al, 2009;Berge et al, 2006;2008;Birringer, 2011;Demirovic and Rattan, 2011;Le Bourg and Rattan, 2008;Mattson, 2008a;Rattan, 2008a;Lima, et al, 2011).…”
Section: S I S Rattan and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such hormetins may be categorized as: (1) physical hormetins, such as exercise, hypergravity, heat and radiation; (2) biological and nutritional hormetins, such as infections, micronutrients, spices and other natural and synthetic compounds; and (3) psychological hormetins, such as mental challenge and focused attention or meditation. Several review and research articles have been published with respect to testing potential anti-aging hormetins, such as heat shock, irradiation, hypergravity, curcumin, kinetin, rosmarinic acid, ferulic acid and food restriction (Barone et al, 2009;Berge et al, 2006;2008;Birringer, 2011;Demirovic and Rattan, 2011;Le Bourg and Rattan, 2008;Mattson, 2008a;Rattan, 2008a;Lima, et al, 2011).…”
Section: S I S Rattan and Othersmentioning
confidence: 99%
“…These tests were done using a blinded-protocol with coded samples at an independent test laboratory "StratiCell" (http://www.straticell.com/) in Belgium under the supervision of the lead author of this article (SISR) during the period August to November 2009. For this purpose, normal human diploid fibroblasts (BJ-HDF), at about 50% lifespan completed in vitro were used under standard cell culture protocols for testing the effects of a compound on cell growth, survival and other biochemical characteristics (Demirovic and Rattan, 2011;Magalhaes et al, 2002;Rattan and Sodagam, 2005). Cells were treated with various doses of Sanchi extracts (LVMH test compound labelled as LVMH2009/1), and were analysed for cell survival by using mitochondrial activity assay MTS and for stress proteins by Western blotting, respectively.…”
Section: Panax Notoginseng (Sanchi) As a Hormetinmentioning
confidence: 99%
“…139 In the integumentary system, an in vitro study demonstrated that curcumin modulates wound healing biphasically, with low doses (1-5 µM) stimulating this homeostatic process, and high doses inhibiting it. 140 This study suggests that curcumin functions as a hormetin by inducing stress response pathways such as Nrf2 and heme oxygenase-1 (HO-1). 140 In one of the first studies investigating the effect of curcumin on the reproductive system, it was discovered that curcumin dose-dependently inhibited the forward motility of both murine and human sperm, the capacitation/acrosome reaction, and murine fertilization in vitro.…”
Section: The Renal Systemmentioning
confidence: 99%
“…The main groups with bioactive properties from these groups are phenolic compounds [8,9]. Ferulic acid, resveratrol, epigallocatechin gallate (EGCG), luteolin, quercetin, and curcumin as phenolic compounds are dose-dependently responsible for the stimulation of kinases and transcription factors and produce a heat shock response, unfolded protein response, autophagic response, DNA repair response, antioxidant response, and sirtuin response [6,[10][11][12][13]. In this chapter, the stress response of dietary phytochemicals will be systematically examined in a hormetic manner for delay of age-related diseases, healthy aging, and longevity based on current data.…”
Section: Introductionmentioning
confidence: 99%